Ibuprofen loaded PLA nanofibrous scaffolds increase proliferation of human skin cells in vitro and promote healing of full thickness incision wounds in vivo. Issue 2 (28th October 2015) - Mohiti‐Asli, M.; Saha, S.; Murphy, S.V.; Gracz, H.; Pourdeyhimi, B.; Atala, A.; Loboa, E. G.
Abstract: This article presents successful incorporation of ibuprofen in polylactic acid (PLA) nanofibers to create scaffolds for the treatment of both acute and chronic wounds. Nanofibrous PLA scaffolds containing 10, 20, or 30 wt % ibuprofen were created and ibuprofen release profiles quantified. In vitro cytotoxicity to human epidermal keratinocytes (HEK) and human dermal fibroblasts (HDF) of the three scaffolds with varying ibuprofen concentrations were evaluated and compared to pure PLA nanofibrous scaffolds. Thereafter, scaffolds loaded with ibuprofen at the concentration that promoted human skin cell viability and proliferation (20 wt %) were evaluated in vivo in nude mice using a full thickness skin incision model to determine the ability of these scaffolds to promote skin regeneration and/or assist with scarless healing. Both acellular and HEK and HDF cell‐seeded 20 wt % ibuprofen loaded nanofibrous bandages reduced wound contraction compared with wounds treated with Tegaderm™ and sterile gauze. Newly regenerated skin on wounds treated with cell‐seeded 20 wt % ibuprofen bandages exhibited significantly greater blood vessel formation relative to acellular ibuprofen bandages. We have found that degradable anti‐inflammatory scaffolds containing 20 wt % ibuprofen promote human skin cell viability and proliferation in vitro, reduce wound contraction in vivo, and when seeded with skin cells, also enhance new blood vessel formation. The approaches and results reported here hold promise for multiple skin tissue engineering and wound healing applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 327–339, 2017.